2019
DOI: 10.1186/s12887-019-1861-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate agreement between the 20-meter shuttle run test and virtual system in healthy children: a cross-sectional study

Abstract: BackgroundEarlier studies evaluated the physiological responses to video games in children with different clinical conditions; however, no study has compared active video games with an incremental field test in healthy children. The purpose of this study was to verify the agreement between the 20-m shuttle run test (20 m-SRT) and virtual system (VS).MethodsThis is a cross-sectional study of 235 children (9.0 ± 0.8 years, 109 boys). The two tests were performed one week apart and the children were instructed no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…However, in the LSD test, a significant difference was observed in the HR scores of the football and handball players in favour of handball. When we examine maximal HR results in studies on basketball, reported that HR of basketball players in 20meter shuttle run test as 198.46 beats/min (Moran et al, 2019). In the current study, it was found to be 196.58 beats/min.…”
Section: Resultssupporting
confidence: 46%
“…However, in the LSD test, a significant difference was observed in the HR scores of the football and handball players in favour of handball. When we examine maximal HR results in studies on basketball, reported that HR of basketball players in 20meter shuttle run test as 198.46 beats/min (Moran et al, 2019). In the current study, it was found to be 196.58 beats/min.…”
Section: Resultssupporting
confidence: 46%
“…Both before and after therapy, patients assessed their fatigue levels using the Borg Rating of Perceived Exertion Scale, the Visual Analogue Scale (VAS), and the modified Medical Research Council (mMRC) dyspnea scale [24][25][26]. Importantly, previous studies have confirmed the effectiveness of using these scales in children [27][28][29].…”
Section: Rating Scales For Dyspnea and Fatiguementioning
confidence: 99%